A robust superhydrophobic PDMS@ZnSn(OH)6 coating with under-oil self-cleaning and flame retardancy. Issue 43 (26th October 2017) - Long, Mengying; Peng, Shan; Deng, Wanshun; Miao, Xinrui; Wen, Ni; Zhou, Qiannan; Yang, Xiaojun; Deng, Wenli
Abstract : The superhydrophobic PDMS@ZHS coating was obtained by pressing superhydrophilic ZHS particles into PDMS and curing agent solutions. Abstract : Some drawbacks such as lack of durability, requirement for high-cost fluorosilane modification, and complicated fabrication processes have limited the practical applications of superhydrophobic coatings for several years. In this work, we provide a novel method to fabricate a robust superhydrophobic coating without pre-modification by pressing ZnSn(OH)6 (ZHS) particles into polydimethylsiloxane (PDMS) solution, and then curing. PDMS used in this work is not only a low surface energy material, but also an adhesive to enhance the bonding force between particles and substrates. The PDMS@ZHS coating (ZHS particles coated on PDMS) is also superhydrophobic when it is immersed into dodecane, and shows excellent self-cleaning in air and oil environments. After undergoing serious chemical corrosion and mechanical abrasion, the superhydrophobicity of the coating remained well. For different kinds of substrates, this coating can be covered and repels water as well. Owing to the excellent flame-retardancy of ZHS particles, PDMS@ZHS coated paper displays excellent flame retardancy in limiting oxygen index (LOI), vertical flame, and cone calorimeter tests. We believe that this simple, environmentally friendly, and versatile fabrication of the PDMS@ZHS coating has excellent real-life applications.